2021
DOI: 10.3390/diagnostics11071155
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Survey of Using Machine Learning in the COVID-19 Pandemic

Abstract: Since December 2019, the global health population has faced the rapid spreading of coronavirus disease (COVID-19). With the incremental acceleration of the number of infected cases, the World Health Organization (WHO) has reported COVID-19 as an epidemic that puts a heavy burden on healthcare sectors in almost every country. The potential of artificial intelligence (AI) in this context is difficult to ignore. AI companies have been racing to develop innovative tools that contribute to arm the world against thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 292 publications
(311 reference statements)
0
31
0
1
Order By: Relevance
“…Consequently, the informativeness of given behavioral parameters is determined not by the number of measured patients, but by the total number of BPIV measurements. BPIV data presented in this study exceeds the most part of statistical studies with a confirmed diagnosis of COVID-19 32,33 . Most of the medical studies on COVID-19 diagnosis based on several hundred analysis data 32,33,34 , while the preliminary study includes data from more than 500,000 measurements of 40 behavioral parameters, and the basic study more than 150,000 measurements of 40 behavioral parameters.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Consequently, the informativeness of given behavioral parameters is determined not by the number of measured patients, but by the total number of BPIV measurements. BPIV data presented in this study exceeds the most part of statistical studies with a confirmed diagnosis of COVID-19 32,33 . Most of the medical studies on COVID-19 diagnosis based on several hundred analysis data 32,33,34 , while the preliminary study includes data from more than 500,000 measurements of 40 behavioral parameters, and the basic study more than 150,000 measurements of 40 behavioral parameters.…”
Section: Discussionmentioning
confidence: 48%
“…BPIV data presented in this study exceeds the most part of statistical studies with a confirmed diagnosis of COVID-19 32,33 . Most of the medical studies on COVID-19 diagnosis based on several hundred analysis data 32,33,34 , while the preliminary study includes data from more than 500,000 measurements of 40 behavioral parameters, and the basic study more than 150,000 measurements of 40 behavioral parameters. Of course, an increase in the amount of data (relative to presented results) may lead to some change in the accuracy of diagnostics, but these changes are unlikely to be of a fundamental nature.…”
Section: Discussionmentioning
confidence: 48%
“…There is no doubt that the world has been facing one of its biggest challenges since the World Health Organization (WHO) declared coronavirus disease (COVID-19) as an epidemic in December 2019 [ 1 ]. The consequences of this epidemic did not affect only the health domain, but also many areas such as the economy, education, and technology [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of this epidemic did not affect only the health domain, but also many areas such as the economy, education, and technology [ 2 ]. COVID-19 is caused by a coronavirus known as severe acute respiratory syndrome two (SARS-CoV-2), which was first identified in Wuhan, China [ 1 , 3 , 4 ]. It is not a new disease, but it is the evolution of an older virus known as SARS-CoV that was also discovered in China in 2003 [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation